Adorable animal quilting : 20+ charming patterns for paper-pieced dogs, cats, turtles, monkeys and more - Alteneder, Ingrid (Page Street Publishing Co., 2020)
Cute, Colorful Quilt Blocks Featuring Your Favorite Animals Discover how fun and easy quilting can be with Ingrid Alteneder's simple paper-piecing patterns featuring adorable animals like cats, turtles, elephants and zebras. Ingrid guides you step by step through everything you need to know to get started, including a complete beginner's guide to foundation paper piecing, 20+ inspiring animal-themed quilt block patterns and templates for every pattern. You'll be amazed at how easy it is to sew colorful, professional-looking quilt blocks for pillows, whole quilts, wall hangings, bags and so much more. Even experienced quilters will find endless inspiration in Ingrid's charming animal world. Add a splash of color to your living room with a bright throw pillow featuring Toni the Toucan or Ali the Alpaca. Give an ocean-themed children's room or nursery a personal, handmade touch with a blanket that showcases Olly the Orca or Sally the Seahorse. Sew Dominic the Dog onto your child's backpack so they can bring their best friend to school every day. With a plethora of fun, lovable animal quilt blocks, everyone will quickly find a favorite project to embark on. Whether you're looking to learn a new craft or enhance your quilting with fresh ideas, Adorable Animal Quilting will have you designing charming quilt blocks all year long.